2014
DOI: 10.1016/j.biologicals.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Type V collagen counteracts osteo-differentiation of human mesenchymal stem cells

Abstract: a b s t r a c tIn search of novel gene signatures for osteo-differentiation of mesenchymal stem cells (MSCs), we submitted cDNA preparations from undifferentiated and differentiating MSCs to differential display-and semiquantitative-PCR and found down-regulation of COL5A1 in osteo-induced cultures at days 21 and 28, when the mineralized matrix accumulates. We also cultured osteo-differentiating MSCs onto type V collagen substrates and found a decrease in the accumulation of extracellular calcium compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(15 reference statements)
0
6
0
1
Order By: Relevance
“…COL11A1 plays an essential role during the cartilage development process ( 32 ). Type V collagen might be considered as a stromal component that impairs osteogenesis ( 33 ). It can be seen that many top 20 DEGs in cluster 2 are related to multidirectional differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…COL11A1 plays an essential role during the cartilage development process ( 32 ). Type V collagen might be considered as a stromal component that impairs osteogenesis ( 33 ). It can be seen that many top 20 DEGs in cluster 2 are related to multidirectional differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the differentiation of stem cells toward osteoblasts depends on numerous signaling pathways and that the process itself could be enhanced and regulated by certain growth factors [8,[238][239][240][241][242]. Some growth factors are already approved by the FDA as drugs for treatment, such as the recombinant human bone morphogenic protein 7 (rhBMP7) in 2001 or the rhBMP2 in 2002 [243,244].…”
Section: Growth Factors Regulation Of Osteogenesis In Dental Stem Cellsmentioning
confidence: 99%
“…[96] It has been used along with various tenogenic inductive treatments, [97][98][99][100] as it facilitates enhanced collagen type I synthesis in vitro. [101,102] Low glucose dose has also been shown [102] Glucose Low doses upregulated expression of scleraxis, SOX9, COL1A1, and COL1A2, but not COL2A [103] TSPCs Tendon-derived matrix Stimulated proliferation and maintained the stemness [216] Collagen type I/fibronectin Demonstrated greater attachment on fibronectin than on collagen [217] Exhibited spindle-shaped morphology with long processes on collagen, but not on fibronectin [217] BMSC Collagen type I Tenogenic differentiation was improved when PDMS replicas of Achilles tendon sections were coated with collagen type I, however this was shown to be concentration-dependent [218] Collagen type I/fibronectin Collagen promoted scleraxis, tenomodulin and tenascin C expression, and inhibited osteogenic differentiation, while fibronectin upregulated RUNX-2 and ALP [91] ADSCs Tendon-derived matrix/fibronectin Deposited more collagen type I and exhibited greater collagen type I to collagen type III ratio on tendon-derived matrix [219] Tendon-derived matrix hydrogel/Collagen type I hydrogel Tendon-derived matrix demonstrated higher proliferation; upregulation of scleraxis, tenascin C, and tenomodulin; enhanced mechanical properties; lower osteogenic potential [220] Collagen type V Reduction of osteogenic differentiation markers, even in the presence of osteogenic media [221] Gelatin Did not show any additional benefits beyond improved adhesion [222] Did not affect proliferation and decreased protein and collagen synthesis [223] 2.7 Tenocyte proliferation was increased at early passage cells [207,212] TSPCs 0.5 Inhibited self-renewal capacity and reduced adipogenic, chondrogenic, and osteogenic potential in differentiation media [224] 2 Increased proliferation, retained their tenogenic differentiation potential, and had a lower osteogenic, chondrogenic, and adipogenic differentiation capacity [212] Reduced Sox-9 and RUNX-2 expression level, did not affect PPAR expression and culture in differentiation media led to enhanced adipogenesis, chondrogenesis, and osteogenesis [225] 5…”
Section: Ecm Proteins and Media Supplementsmentioning
confidence: 99%